Development and validation of modified QuEChERS- GC/MS method for simultaneous determination of current-use pesticide residues in soil - Nguyen, Thi Hong; Huynh, Vinh Nhan; Trinh, Ngoc Bang Thanh; Ngo, Thi Thanh Xuan; Le, Lam Son; Nguyen, Duc Cuong; Nguyen, Dang Giang Chau; Huynh, Thi Tuy Ngoc (Hue University Journal of Science: Natural Science, 2026)
Pesticide residues in soil pose potential risks to ecosystems and human health, necessitating reliable and efficient analytical methods for their determination. This study developed and validated a modified QuEChERS-based extraction procedure combined with gas chromatography-mass spectrometry (GC/MS) for the simultaneous analysis of eight commonly used pesticides in soil, including herbicides, insecticides, and fungicides. Key extraction parameters were optimised for soil matrices, focusing on solvent composition and primary-secondary amine (PSA) clean-up levels. Optimal performance was achieved with 1% acetic acid in acetonitrile and 25 mg PSA per 1 mL of extract. The method was validated according to European Commission SANTE guidelines, demonstrating good linearity (R² > 0.99), low limits of detection (3–8 µg/kg), acceptable recoveries (69–114%), and satisfactory repeatability (RSD < 13%). The validated procedure was successfully applied to agricultural soil samples from central Vietnam, where residues of pretilachlor, fluazifop-p-butyl, and trifloxystrobin were detected. The results confirm that the proposed method is reliable, cost-effective, and suitable for routine monitoring of pesticide residues in soil.